VIR and Leningrad Quarantine Laboratory: 90 years of cooperation - E. V. Drugova; T. M. Ozerskaya (Труды по прикладной ботанике, генетике и селекции)
The history of Leningrad Quarantine Laboratory, a subdivision of the Soviet and Russian phytosanitary services, is discussed. Its interaction and cooperation with the All-Union Research Institute of Plant Industry (later: N.I. Vavilov All-Russian Institute of Plant Genetic Resources, VIR) are reviewed. The background of the need to organize such laboratory, its main activities, and the changes that followed are also explained.Leningrad Quarantine Laboratory has always closely collaborated with VIR. It has been accommodated within the Institute’s premises for 75 years. Such proximity has facilitated and accelerated the access to the plant germplasm received by VIR for plant protection and quarantine experts. Thus, a unique combination of phytosanitary safety and research activities was achieved. At the same time, the laboratory turned out to be an important research institution, publishing scientific works and methodological guidelines in the field of plant protection.In the course of its activities, the laboratory staff improved the existing methods and developed new ones for phytosanitary control of plant germplasm and its protection against pests, weeds, and pathogenic microorganisms. Manuals, directories, and identification guides written by the laboratory staff still remain the reference books for quarantine and plant protection experts. The laboratory was also very important as a qualification improvement facility for such experts. All these functions have become possible because of the work with plant germplasm that arrived to the VIR collection.